2013
DOI: 10.1016/j.jpsychires.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met modifies the risk of childhood trauma on obsessive-compulsive disorder

Abstract: Abstract:Childhood trauma has been linked to the development of later psychopathology, including obsessive-compulsive disorder (OCD). Although evidence exists to suggest that genetic and environmental factors are involved in the aetiology of OCD, little attention has been paid to the interactions that exist between genes and environment. The aim of this study was to investigate gene-byenvironment interactions between childhood trauma and the BDNF Val66Met variant in patients with OCD.Childhood trauma was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
2
38
0
1
Order By: Relevance
“…25 The MAOA and DAT genes necessitated adjustment for home language with the group comparisons (previous work by our group found that using language as a proxy for population structure served well in statistically correcting for this factor, if applicable 26 ). Clinical and genetic data were compared between patients with primary symmetry concerns and/or compulsions and those without these symptoms by using ANOVAs and chi-square tests as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…25 The MAOA and DAT genes necessitated adjustment for home language with the group comparisons (previous work by our group found that using language as a proxy for population structure served well in statistically correcting for this factor, if applicable 26 ). Clinical and genetic data were compared between patients with primary symmetry concerns and/or compulsions and those without these symptoms by using ANOVAs and chi-square tests as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as seen in the evidence base for obsessive compulsive disorder (Hemmings et al, 2013), research should now consider the interaction with a genetic predisposition and replicating in a clinical population (Monzani et al, 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…The first association study between and Val66Met was in 2003, reporting that the allele Met66 showed a protective effect on OCD (Hall et al, 2003). However the following studies showed inconsistent results (Alonso et al, 2008;Wendland et al, 2007;Zai et al, 2005), some even said that Met66 was a risk allele for OCD (Hemmings et al, 2008;Hemmings et al, 2013). There have been already several meta-analysis in different kinds of mental disorders, such as depression, bipolar disorders, schizophrenia, anorexia nervosa and drug abuse (Brandys et al, 2013;Gonzalez-Castro et al, 2014;Gyekis et al, 2013;Harrisberger et al, 2014;Kanazawa et al, 2007;Verhagen et al, 2010).…”
mentioning
confidence: 99%